Analisis Pengaruh Manajemen Kas Dalam Proses Pengambilan Keputusan - Sandra Iriawan; Windy Sharlina Indrianti; Hikmahwati (P3M Politeknik Negeri Banjarmasin, 2023)
Manufacturing companies in making their products must carry out activities as effectively and efficiently as possible, including by calculating the cost of goods manufactured appropriately. Donat Ardika is a micro-scale manufacturing company. The calculation of the cost of goods manufactured by Donat Ardika is still not in accordance with the concept of cost accounting because it has not classified the right costs and has never calculated the amount of depreciation of fixed assets so that it affects the recognition of profits calculated by the company. This study aims to calculate the cost of goods sold at Donat Ardika. The type of research conducted is a case study with a descriptive approach. The data collection methods used are interview and documentation methods. The results showed that there were differences in the calculation of the cost of goods between what the company did and what used the full costing method. The difference in charging production costs carried out by the company affects the calculation of gross profit received so that there is a difference in gross profit of Rp 115,531,563.